2001
DOI: 10.1021/jp9934331
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Kinetics of CO2, O2, N2, and CH4 in Cation-Exchanged Clinoptilolite

Abstract: The rate of adsorption of pure CO 2 , O 2 , N 2 , and CH 4 on natural untreated clinoptilolite-rich volcanic tuff (Cp) from Tehuacan (Puebla, Mexico), and on cation-exchanged clinoptilolite samples (Ca-Cp, K-Cp, and Na-Cp) has been measured at 20 °C using a glass high-vacuum volumetric apparatus. The X-ray diffraction pattern of Cp showed that the main crystalline phases correspond to clinoptilolite-heulandite and minor amounts of mordenite, cristobalite, feldspar (albite), quartz, smectite, and opal. The adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 13 publications
1
54
0
Order By: Relevance
“…For example, the erionites, mordenites, clinoptilolites and chabazite can adsorb only the molecules which possess kinetic diameter with a maximum of 4.3, 3.9, 3.5-3.8 and 4.3 Å, respectively, indicating that the CO 2 adsorption (diameter = 3.3 Å) is not limited by this steric factor [12,16,43,57]. Moreover, it has been showed by Aguilar-Armenta et al [7] that the require period for reach the middle of the capacity of CO 2 , O 2 or N 2 adsorption on Na-clinoptilolite and Caclinoptilolite is proportional to diameter of the adsorbed molecules (CO 2 < O 2 < N 2 ).…”
Section: Influence Of the Dimension Of Adsorbatesmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, the erionites, mordenites, clinoptilolites and chabazite can adsorb only the molecules which possess kinetic diameter with a maximum of 4.3, 3.9, 3.5-3.8 and 4.3 Å, respectively, indicating that the CO 2 adsorption (diameter = 3.3 Å) is not limited by this steric factor [12,16,43,57]. Moreover, it has been showed by Aguilar-Armenta et al [7] that the require period for reach the middle of the capacity of CO 2 , O 2 or N 2 adsorption on Na-clinoptilolite and Caclinoptilolite is proportional to diameter of the adsorbed molecules (CO 2 < O 2 < N 2 ).…”
Section: Influence Of the Dimension Of Adsorbatesmentioning
confidence: 85%
“…In this matter, an analysis of the CO 2 adsorption on zeolites KX, BaX and LaX has effectively indicated that the zeolite KX was the most basic among these three zeolites [28]. In contrast, a study of CO 2 adsorption on the clinoptilolite has indicated that the substitution of Na + and K + by Ca 2+ caused a rise of the basicity of the framework oxygen acting as basic center [7]. The basic strength and the capacity of CO 2 adsorption of zeolites might also be increased significantly by occlusion of alkali metal oxides.…”
Section: Influence Of the Structural Characteristics Of Zeolites On Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicate that the generation of negative charge of aluminosilicate minerals is due to the isomorphic substitution between silicon and aluminum atoms. The adsorption properties of gaseous substances depend largely on the exchangeable cations that are much more important for zeolites with a porous structure 23,24) .…”
Section: Cation Exchange Capacitymentioning
confidence: 99%
“…Low-temperature Adsorbents. Low-temperature adsorbents mainly including zeolite based adsorbents [4,5], carbon based adsorbents [6,7] and metal organic framework based adsorbents [8][9][10] always have received extensive attention, especially in recent years. Zeolites are porous crystalline aluminosilicates, whose framework of SiO 4 and AlO 4 joined together in various regular arrangements through shared oxygen atoms.…”
Section: Types Of Co 2 -Adsorbents By the Adsorption Temperaturementioning
confidence: 99%